2021
DOI: 10.1182/bloodadvances.2020004144
|View full text |Cite
|
Sign up to set email alerts
|

Response to upfront azacitidine in juvenile myelomonocytic leukemia in the AZA-JMML-001 trial

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is the only curative therapy for most children with juvenile myelomonocytic leukemia (JMML). Novel therapies controlling the disorder prior to HSCT are needed. We conducted a phase 2, multicenter, open-label study to evaluate the safety and antileukemic activity of azacitidine monotherapy prior to HSCT in newly diagnosed JMML patients. Eighteen patients enrolled from September 2015 to November 2017 were treated with azacitidine (75 mg/m2) administered I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…In recent years, knowledge about disease heterogeneity, pathobiology, and treatment in JMML has improved a lot 13,26 . Now, 5‐azacitidine is used as a good bridge to HSCT, with patients showing a better performance status for the curative treatment 15,17 . MFC has already shown to be feasible in JMML diagnosis with immunophenotypic characteristics similar to those found in MDS but not CMML 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, knowledge about disease heterogeneity, pathobiology, and treatment in JMML has improved a lot 13,26 . Now, 5‐azacitidine is used as a good bridge to HSCT, with patients showing a better performance status for the curative treatment 15,17 . MFC has already shown to be feasible in JMML diagnosis with immunophenotypic characteristics similar to those found in MDS but not CMML 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…5‐Azacitidine (5‐aza) is a DNA‐hypomethylating agent that proved to be efficient in adult myelodysplastic syndrome (MDS) patients and has also been used in JMML as a bridge to HSCT 14–17 . Response criteria have been developed based mainly on leukocyte count and spleen size 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…If necessary, the choice of bridge to transplant therapy remains uncertain [39]. Interestingly, in a recent trial, the hypomethylating agent azacitidine demonstrated to provide a relevant clinical benefit in newly diagnosed JMML prior to HSCT, but patients with CBL mutations were excluded [40].…”
Section: Cbl In Jmmlmentioning
confidence: 99%
“…DNA hypermethylation has been showed to be a hallmark in the most aggressive cases of JMML [ 25 , 37 , 99 ]. For that reason, the use of the DNA methyltransferase inhibitor azacitidine has been explored as a potential therapeutic agent for the treatment of this disease, alone or in combination with conventional cytotoxic chemotherapy [ 116 ]. Azacitidine use in JMML was first reported on a patient that achieved complete clinical and genetic remission of the disease after eight cycles of treatment prior to HSCT [ 117 ].…”
Section: Genetic and Epigenetic Therapeutic Targets For The Treatment...mentioning
confidence: 99%
“…Later on, a retrospective study showed that low-dose azacitidine was effective and tolerable in JMML, and documented another three JMML cases in which this drug induced complete remission before HSCT [ 118 ]. Finally, the beneficial effects of pre-HSCT azacitidine treatment were formally validated in a phase II clinical trial (NCT02447666) that demonstrated that the use of this drug as a single agent is a suitable option for newly diagnosed JMML patients, independent of their methylation status [ 116 ]. In addition, the histone deacetylase inhibitor vorinostat, is currently being explored in a phase I clinical trial (NCT03843528) in combination with low dose azacitidine for the treatment of pediatric myeloid malignancies, including JMML.…”
Section: Genetic and Epigenetic Therapeutic Targets For The Treatment...mentioning
confidence: 99%